Lucian's Hippias - Thonemann, P (Cambridge University Press, 2023)
Lucian's Hippias or The Bath, traditionally considered to be a straight-faced encomium of a historical architect and real-life bath-house of the Antonine period, is now often judged to be a work of satire, though what exactly is being satirized has remained elusive. This article argues that the architect ‘Hippias’ is closely modelled on Plato's caricature of the sophist Hippias of Elis in the Hippias Minor, and that his bath-house is a comic extrapolation from the sophist's home-made oil-flask and strigil. Lucian's Hippias should be read as a parody of contemporary prose encomia of public buildings.